2010
DOI: 10.1016/j.jveb.2010.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a diet containing caseinate hydrolysate on signs of stress in dogs

Abstract: The purpose of this randomized, double-blind, placebo-controlled trial was to evaluate the efficacy of a diet containing caseinate hydrolysate (CH) on signs of stress in 2 groups of dogs (defined as Anxious and Nonanxious), using physiological (serum cortisol and lysozyme, N:L ratios and heart rate) and behavioral parameters.From an initial group of 40 female Beagle dogs, ranging in age from 10 months to 4 years (mean 5 1.47 years; SD 5 0.53) belonging to a dog colony, 32 were selected for this study according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…However, some owners may be hesitant to administer such medications, whether due to the possibility of undesirable side effects, personal bias against drug use, or cost. This has led to increased interest in the use of natural extract products to alter fearful behaviors, like dog-appeasing pheromones or oral supplementations such as L-theanine, a tryptic hydrolysate of milk protein and fish hydrolysate (8)(9)(10)(11)(12). Additionally, there has been renewed interest in the use of cannabinoids, cannabidiol (CBD) in particular, to regulate anxiety disorders in both humans and companion animals (13).…”
Section: Introductionmentioning
confidence: 99%
“…However, some owners may be hesitant to administer such medications, whether due to the possibility of undesirable side effects, personal bias against drug use, or cost. This has led to increased interest in the use of natural extract products to alter fearful behaviors, like dog-appeasing pheromones or oral supplementations such as L-theanine, a tryptic hydrolysate of milk protein and fish hydrolysate (8)(9)(10)(11)(12). Additionally, there has been renewed interest in the use of cannabinoids, cannabidiol (CBD) in particular, to regulate anxiety disorders in both humans and companion animals (13).…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety disorders are common in veterinary species, regularly leading to behavioural responses which are reported as being problematic (Dreschel, 2010). Unfortunately, as Roshier and McBride (2013) explains, there is poor and incomplete recognition of animal behaviour within the veterinary profession, and, whilst research documenting specific psychological disorders in dogs is evident (Cannas et al, 2010;Palestrini et al, 2010), little in known in relation to epileptic patients. Shihab et al (2011) found significantly increased anxiety in dogs following IE onset, assessed using the Canine Behavioural Assessment and Research Questionnaire.…”
Section: Anxiety Disorders As a Comorbidity In Dogsmentioning
confidence: 99%
“…Two of these studies (Palestrini et al, 2010;Kato et al, 2012) investigated the use of diets with added alphacasozepine, though, in the Kato et al (2012) study the diet was also supplemented with another compound (tryptophan) thought to have anxiolytic properties. The remaining study (Beata et al, 2007) investigated the use of a daily capsule of alpha-casozepine.…”
Section: The Evidencementioning
confidence: 99%
“…The remaining study (Beata et al, 2007) investigated the use of a daily capsule of alpha-casozepine. The two studies focused on dietary interventions (Palestrini et al, 2010; Kato et al, 2012) used a placebo-controlled study design, whereas Beata et al (2007) compared alphacasozepine to another intervention (selegiline) that was already used commercially as an anxiolytic.…”
Section: The Evidencementioning
confidence: 99%